Perubahan Struktur Ekonomi, Dekomposisi Sumber Pertumbuhan Output, dan Pertumbuhan Total Factor Productivity (TFP): Analisis Lanjutan Tabel Input-Output Provinsi Kalimantan Selatan, 2000-2010 - Nurul Fajri; Mudrajad Kuncoro (Universitas Negeri Malang, 2016)
Economic growth can be seen from the aggregate demand side, namely consumption, investment, government spending, exports and imports, and the aggregate supply side namely labor growth, capital growth and the growth of TFP (Total Factor Productivity). This study uses South Kalimantan’s Input-Output Tables of 2000, 2005 and 2010. The results showed that although the structure of the value-added of the mining sector remains the main economic pillar, but this sector has low linkages with other sectors. Based Multiplier Product Matrix, manufacturing industry suggest a leading role in the economy so that it can be said that the province of South Kalimantan are heading toward a change in the economic structure. Decomposition of sources of growth based on the Chenery’s model (1960) showed that the main source of economic growth in South Kalimantan is exports by 67 percent in the period 2000-2005 and 73.72 percent in the period 2005-2010, especially the export of coal. Decomposition of productivity growth made by Namura and Kuroda’s model (2004) and suggests that TFP growth and capital have a strong linear relationship and significant Output growth, while labor productivity have no significant correlation with Output growth. Finally, the wealth of the abundant natural resources, industry-oriented economic growth and sustainable development in South Kalimantan Province is agriculture-based industries and mining-based industries with the main strategy is to import substitution and investment in capital and technology.Keywords: Input-Output Tables, Multiplier Product Matrix, Decomposition of output growth, Total Factor ProductivityJEL Classification: C67, O47